AN EXPERIMENTAL STUDY OF WATER AND CARBON DIOXIDE SOLUBILITIES IN MID-OCEAN RIDGE BASALTIC LIQUIDS. PART I: CALIBRATION AND SOLUBILITY MODELS - Dixon Ja.E.; Stolper E.M.; Holloway J.R. (My University, 1995)
Experiments were conducted to determine the solubilities of H2O and CO2 and the nature of their mixing behavior in basaltic liquid at pressures and temperature relevant to seqfloor eruption. Mid-ocean ridge basaltic (MORB) liquid was equilibrated at 1200°C with pure H2O at pressures of 176–717 bar and H2O—CO2 vapor at pressures up to 980 bar. Concentrations and speciation of H2O and CO2 dissolved in the quenched glasses were measured using IR spectroscopy. Molar absorptivities for the 4500 cm?1 band of hydroxyl groups and the 5200 and 1630 cm?1 bands of molecular water are 0,67±0,03, 0,62±0,07, and 25±3 l/mol-cm, respectively. These and previously determined molar absorptivities for a range of silicate melt compositions correlate positively and linearly with the concentration of tetrahedral cations (Si+Al). The speciation of water in glass quenched from vapor-saturated basaltic melt is similar to that determined by Silver & Stolper (Journal of Petrology 30, 667–709, 1989) in albitic glass and can be fitted by their regular ternary solution model using the coefficients for albitic glasses. Concentrations of molecular water measured in the quenched basaltic glasses are proportional to f H2O in all samples regardless of the composition of the vapor, demonstrating that the activity of molecular water in basaltic melts follows Henrys law at these pressures. A best fit to our data and existing higher-pressure water solubility data (Khitarov et al., Geochemistry 5, 479–492, 1959; Hamilton et al., Journal of Petrology 5, 21–39, 1964), assuming Henrian behavior for molecular water and that the dependence of molecular water content on total water content can be described by the regular solution model, gives estimates for the Vo, mH2O of 12±1 cm3/mol and for the 1-bar water solubility of 0,11 wt%. Concentrations of CO2 dissolved as carbonate in the melt for pure CO2-saturated and mixed H2O-CO2-saturated experiments are a simple function of fCO2 These results suggest Henrian behavior for the activity of carbonate in basaltic melt and do not support the widely held view that water significantly enhances the solution of carbon dioxide in basaltic melts. Using a ?Vo, mr of 23 cm3/mol (Pan et al., Geochimica et Cosmochimica Acta 55, 1587–1595, 1991), the solubility of carbonate in the melt at 1 bar and 1200°C is 0,5 p.p.m. Our revised determination of CO2 solubility is ~20% higher than that reported by Stolper & Holloway (Earth and Planetary Science Letters 87, 397–408, 1988).